Membangun Jaringan Internet Kampung berbasis Hostpot RT/RW di kelurahan Kemas Rindo Palembang - Zulhipni Reno Saputra Elsi; Sri Primaini; Hartini Hartini (UNIVERSITAS INDO GLOBAL MANDIRI)
The internet is a communication tool to find the information needed, not all areas are covered by the internet. Internet service providers as internet service providers also offer expensive packages beyond the ability of residents, in this study designing an internet network in Kemas Rindo village to help residents get cheap and good internet facilities. In this study using the waterfaal method in building an internet network, analysis, design, coding, testing and maintenance were carried out. Based on the area of 3027 hectares and the number of community units as many as 8 RWs in the Kemas Rindo sub-district, 8 CPE points were built with Bridge mode. After finishing building the internet network, Quality of Service measurements were made on Throughput, Packet Loss, Delay (latency), Jitter and the results obtained were categorized as good or with an index value of 3 based on the reference value of Telecommunications and Internet Protocol Harmonization Over Networks (TIPHON). The value obtained from the QoS measurement is throughput of 81.125, Packet Loss of 0.375, Delay of 150,625 and Jitter of 0.500. Keywords : Hostpot, RT RW Net, Kemas Rindo, Waterfall, QoS